2019
DOI: 10.1038/s41594-019-0261-7
|View full text |Cite
|
Sign up to set email alerts
|

Damage sensor role of UV-DDB during base excision repair

Abstract: UV-DDB, a key protein in human global nucleotide excision repair (NER), binds avidly to abasic sites and 8-oxo-guanine (8-oxoG), suggesting a non-canonical role in base excision repair (BER). We investigated whether UV-DDB can stimulate BER for these two common forms of DNA damage, 8-oxoG and abasic sites, which are repaired by 8-oxoguanine glycosylase (OGG1) and apurinic/apyrimidinic endonuclease (APE1), respectively. UV-DDB increased both OGG1 and APE1 strand cleavage and stimulated subsequent DNA polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(126 citation statements)
references
References 66 publications
6
120
0
Order By: Relevance
“…In addition, OGG1 activity can be influenced by many other factors. Recently, it has been shown that UV-DDB stimulates OGG1 incision activity 43 . Notably, a significant correlation was observed between the protein levels of DDB1 and OGG1 in both NMIBC and in the corresponding normal tissues, although DDB1 does not appear to be responsible for the lack of correlation between OGG1 protein and activity levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, OGG1 activity can be influenced by many other factors. Recently, it has been shown that UV-DDB stimulates OGG1 incision activity 43 . Notably, a significant correlation was observed between the protein levels of DDB1 and OGG1 in both NMIBC and in the corresponding normal tissues, although DDB1 does not appear to be responsible for the lack of correlation between OGG1 protein and activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…OGG1 enzyme activity did not correlate significantly with its protein level in NMIBC and the corresponding normal tissue (p > 0.05) ( Supplementary Table S3 online). As a recent report has suggested that DNA damage binding protein 1 (DDB1), a protein that is a component of the UV-DDB DNA damage recognition complex, exhibits the ability to stimulate OGG1 activity 43 , we examined the levels of DDB1 in NMIBC and corresponding normal tissue extracts. We observed a significant correlation between the protein levels of DDB1 and OGG1 in NMIBC tissues (r = 0.57, p = 0.02) and in the corresponding normal tissues (r = 0.86, p = 0.0001) ( Supplementary Fig.…”
Section: Nmibc Tissues Have Increased Uracil Incision Activity But Nmentioning
confidence: 99%
“…Moreover, the binding of UV-DDB seems to precede the activity of ATP-mediated chromatin remodelers ( 53 , 54 ). More recently, as discussed in the last section, our group has demonstrated that the oxidative base damage 8-oxoG, which only causes a mild helix distortion, is recognized by UV-DDB in naked duplex DNA, as well as in living cells ( 55 , 56 ). The relatively mild nucleosome distortion caused by CPD and 8-oxoG is analogous to cyPu.…”
Section: Could Cyclopurine Deoxynucleosides Explain Neurodegenration mentioning
confidence: 92%
“…UV-DDB is known to recognize and bind sites of UV damage, but has also been shown to bind more strongly to a short DNA duplex containing an abasic site, as compared to a DNA substrate containing a CPD, suggesting a possible role for UV-DDB in BER ( 96 , 97 ). In order to directly test this hypothesis, we recently investigated whether UV-DDB plays an important role in initiating the repair of 8-oxoG lesions ( 56 ). It should be noted that previous studies missed that UV-DDB was able to discriminate between non-damaged DNA and DNA containing 8-oxoG ( 96 ).…”
Section: A New Role Of Uv-ddb In the Removal Of 8-oxogmentioning
confidence: 99%
“…Given the important role of linker histones in higher-order chromatin folding 56 it is tempting to speculate that DDB2 triggers damaged chromatin decompaction at least in part by promoting H1 displacement. Importantly, the function of DDB2 in regulating chromatin compaction likely extends to other types of DNA lesions than those processed by the NER pathway considering that DDB2 also detects oxidative damage and contributes to base excision repair 78,79 .…”
Section: Regulation Of Heterochromatin Compaction Following Uv Damagementioning
confidence: 99%